Jackson-type inequalities and exact values of widths of classes of functions in the spaces $S^p , 1 ≤ p < ∞$ - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
In the spaces $S^p , 1 ≤ p < ∞$, introduced by Stepanets, we obtain exact Jackson-type inequalities and compute the exact values of widths of classes of functions determined by averaged moduli of continuity of order $m$.